2005
DOI: 10.1261/rna.2230605
|View full text |Cite
|
Sign up to set email alerts
|

A kissing-loop interaction in a hammerhead viroid RNA critical for its in vitro folding and in vivo viability

Abstract: Chrysanthemum chlorotic mottle viroid (CChMVd) RNA (398-401 nucleotides) can form hammerhead ribozymes that play a functional role in its replication through a rolling-circle mechanism. In contrast to most other viroids, which adopt rod-like or quasi-rod-like secondary structures of minimal free energy, the computer-predicted conformations of CChMVd and Peach latent mosaic viroid (PLMVd) RNAs are branched. Moreover, the covariations found in a number of natural CChMVd variants support that the same or a closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 33 publications
9
55
0
9
Order By: Relevance
“…However, we found that the minimal free-energy secondary structure predicted for GHVd RNA (Fig. 3A) displayed remarkable similarity to that of PLMVd (2,27,28). The secondary structure of PLMVd contains a long branched region stabilized by a kissing-loop pseudoknot and an extensively base-paired arm that encodes two self-cleavable hammerhead ribozymes active in the plus and minus strands, respectively (2,27,28).…”
Section: Resultsmentioning
confidence: 87%
“…However, we found that the minimal free-energy secondary structure predicted for GHVd RNA (Fig. 3A) displayed remarkable similarity to that of PLMVd (2,27,28). The secondary structure of PLMVd contains a long branched region stabilized by a kissing-loop pseudoknot and an extensively base-paired arm that encodes two self-cleavable hammerhead ribozymes active in the plus and minus strands, respectively (2,27,28).…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, we have not detected by native PAGE any Mg 2+ -induced difference in the mobility of the mc ASBVd (À) RNA, while we have observed for it a slower mobility than for its (+) counterpart that neither is influenced by Mg 2+ . This latter result, particularly, argues against the existence of a kissing-loop interaction in the mc ASBVd (À) RNA because an interaction of this kind in CChMVd causes a faster mobility consistent with a more compact folding [39], in contrast with the results observed in the coelectrophoresis of the mc ASBVd (+) and (À) RNAs (Fig. 2b).…”
Section: Discussionmentioning
confidence: 77%
“…2a), without dismissing the coexistence of others with minor changes undetectable by non-denaturing PAGE. The lack of noticeable Mg 2+ effects did not favour the presence of tertiary interactions like the kissing loops reported in peach latent mosaic viroid (PLMVd) and chrysanthemum chlorotic mottle viroid (CChMVd) [38,39].…”
Section: Resultsmentioning
confidence: 87%
“…Este tipo de interacciones tiene importancia biológica ya que una alteración de la secuencia de estas zonas provoca la perdida de infectividad como se ha descrito in vivo mediante experimentos de mutagénesis dirigida en CChMVd (Gago et al 2005).…”
Section: Familia Avsunviroidaeunclassified
“…Mutants were generated following a PCR-based protocol (Byrappa et al, 1995) with minor modifications (Gago et al, 2005). Briefly, 5 ng of a derivative of plasmid pBluescript II KS (+) containing the full-length viroid sequence were amplified with 250 ng each of pairs of adjacent and phosphorylated primers, complementary and homologous to different segments of the viroid sequence, in which appropriated changes were introduced to incorporate the desired mutations (Table 1).…”
Section: Short Communicationmentioning
confidence: 99%